Global Rice Paddy Inventory (GRPI): A high-resolution inventory of methane emissions from rice agriculture based on landsat satellite inundation data - Chen, Zichong; Lin, Haipeng; Balasus, Nicholas; Hardy, Andy; East, James D.; Zhang, Yuzhong; Runkle, Benjamin R. K.; Hancock, Sarah E.; Taylor, Charles A.; Du, Xinming; Sander, Bjoern Ole; Jacob, Daniel J. (American Geophysical Union (AGU), 2025)
Rice agriculture is a major source of atmospheric methane, but current emission inventories are highly uncertain, mostly due to poor rice-specific inundation data. Inversions of atmospheric methane observations can help to better quantify rice emissions but require high-resolution prior information on the location and timing of emissions. Here we use Landsat satellite data at 30 m resolution to map the global monthly distribution of rice paddy fractional areas on a 0.1° × 0.1° (∼10 × 10 km) grid by optimizing an algorithm for flooded vegetation and combining it with a 30 m global cropland database and rice-specific data. We validate this global rice paddy map with an independent US rice database and with seasonal flux measurements from the FLUXNET CH4 network, estimating errors on rice area fraction of 31% on the 0.1° × 0.1° grid and 10% regionally. We combine the rice paddy map with an extensive global data set of emission factors (EFs) per unit of rice paddy area. The resulting Global Rice Paddy Inventory (GRPI) provides methane emission estimates at 0.1° × 0.1° (∼10 × 10 km) spatial resolution and monthly resolution. Our global emission of 39.3 ± 4.7 Tg a−1 for 2022 (best estimate and error standard deviation) is higher than previous inventories that use outdated rice maps and IPCC-recommended EFs now considered to be too low. China is the largest rice emitter in GRPI (8.2 ± 1.0 Tg a−1), followed by India (6.5 ± 1.0 Tg a−1), Bangladesh (5.7 ± 1.2 Tg a−1), Vietnam (5.7 ± 1.0 Tg a−1), and Thailand (4.4 ± 0.9 Tg a−1). These five countries together account for 78% of global total rice emissions. Seasonality of emissions varies considerably between and within individual countries reflecting differences in climate and crop practices. We define a rice methane intensity (methane emission per unit of rice produced) to assess the potential of mitigating methane emission without compromising food security. We find national methane intensities ranging from 10 to 120 kg methane per ton of rice produced (global mean 51) for major rice-growing countries. Countries can achieve low intensities with high-yield cultivars, upland rice agriculture, water management, and organic matter management.